Análise da planta genérica de valores por meio de estrato de renda no município de São Carlos - Medvedchikoff, Tatiana Gakiya (Universidade Federal de São Carlos, 2009)
The tax planning is necessary for there to be a rational application of resources and improvements in basic infrastructure for the municipality. Therefore, the assessment and questioning of the results indicated in the Generic Plant Values can provide information to the legitimacy of taxation more fair and accessible. This study evaluated the consistency of values existing plant in São Carlos - SP with respect to income levels provided by the Brazilian Institute of Geography and Statistics (IBGE). The methodology used algebra through the Spring software. The results indicated possible inconsistencies between the income strata and venal values established. It is concluded that the plant venal values could be more efficient if they changed the criteria for charging for urban voids and taken into account the income strata of the taxpayer.
Keywords: Planejamento urbano; Planta de valores genéricos; Tributos municipais; Valor venal; Geoprocessamento; Sistemas de informação geográfica; Tributação; Estratos de renda; Generic plant values; Municipal taxes; Venal value; GIS; Geographic information systems; Strata; ENGENHARIAS